AKTIVITAS ANTIOKSIDAN, TOTAL FENOL, TOTAL FLAVONOID, TOTAL KAROTENOID DARI BERBAGAI EKSTRAK BIJI ALPUKAT (PERSEA AMERICANA MILL.) DAN ISOLASI SENYAWA ANTIOKSIDAN - Jennita
A free radical is an atom or atom group that contain unpaired electron. An unpaired electron can make the free radical be reactive by attacking and binding to other molecules electron. Various possibilities can occur as a result of free radical, example, malfunctioning of cell and damage of cells structure. Antioxidant is a compound that can inhibit the oxidation reaction by attacking and binding free radical, therefore, damage cell will be inhibited. Based on several studies, avocado (Persea americana Mill.) seed was known to have antioxidant activity. In addition, avocado seed has been used for treating various diseases, such as lowering blood glucose level and treating bacterial infection. This research aimed to determine IC50 of DPPH scavenging activity; determine total phenolic, total flavonoids, and total carotenoid of each extract, analyze the correlation between total phenolic, total flavonoids, and total carotenoid with IC50 of DPPH scavenging activity; and isolation of antioxidant compound. Crude drug of avocado seed was extracted by reflux using three solvents with increasing polarity, i.e. n-hexane, ethyl acetate and ethanol. Each extract was monitored by thin layer chromatography (TLC). The IC50 of DPPH scavenging activity, total phenolic, total flavonoid, total carotenoid of each extract was monitored by ultraviolet-visible spectrophotometry. Correlation of total phenolic, flavonoids, and carotenoid with IC50 of DPPH scavenging activity was analyzed using Pearson’s method. The ethyl acetate extract was fractionated by vacuum liquid chromatography, and the fractions 16-18 were then subfractionated by column chromatography. Subfraction 44 and 45 were collected and purified by washing using n-hexane and by TLC preparative. The isolate was characterized using specific spray reagent, ultraviolet-visible spectrophotometry, two-dimentional paper chromatography, and infrared spectrophotometry. Crude drug of avocado seed contained alkaloids, flavonoids, tannins, terpenoids, steroid/triterpenoid, and phenolic compounds. The ethanol extract gave the highest antioxidant activity, by showing the lowest IC50 of DPPH scavenging activity (0.97 ± 0.29) µg/mL. The highest flavonoid and carotenoid total content were given by n-hexane extract i.e. 2.74 ± 0.07 g QE/100 g and 0.58 ± 0.09 g BE/100 g, respectively. The highest total phenolic content was given by ethanol extract (9.12 ± 0.20) g GAE/100 g. The IC50 of DPPH scavenging activity of n-hexane, ethyl acetate, and ethanol extracts were 38.06 µg/mL, 2.71 µg/mL, and 0.97 µg/mL. Total phenolic content had negatively high correlation with antioxidant activity from avocado seed extract. Phenolic compound were the major contributor of antioxidant activity in avocado seed extract using DPPH assay. An isolated antioxidant compound was obtained from ethyl acetate extract and was supposed to be an isoflavone glycoside having free –OH groups in ring A and or B.